Subwavelength ultrasonic imaging via a harmonic resonant tunneling metalens - Hur, Shin; Jeon Ho yoon; Anzan-Uz-Zaman, Md; Kim, Youngsoo; Shah, Muhammad A.; Kim, Jinsik; Lee, Byung Chul (Pergamon Press Ltd., 2022)
Resonant tunneling metalenses have excellent applications for subwavelength ultrasonic imaging in air. In this study, an acoustic metalens intended for underwater imaging was designed with first, second, and third resonant tunneling frequencies of 10.3, 85.3, and 105.9 kHz, respectively. The resonant tunneling metalens and letter-shaped validation specimens were fabricated via additive manufacturing using polymers. Before the underwater experiment, an array of 36 channels of lead zirconate titanate elements was installed at the bottom of a test water tank to generate ultrasonic waves. Next, the resonant tunneling metalens and one of the letter-shaped specimens were placed in the tank, and ultrasonic imaging was performed with a needle-type hydrophone. Experimental results at the third resonant tunneling frequency confirmed that subwavelength ultrasonic imaging of the letter-shaped specimen was possible at a minimum level of λ/13.98. Therefore, the proposed metalens is shown to be suitable for high-resolution ultrasound applications such as biomedical and non-destructive imaging.